The effect of Profitability and Stock Split on Stock Return - Fajar Nurdin; Fadlil Abdani (Universitas Padjadjaran, 2020)
Purpose of the study is to examine the effect of profitability and stock split on stock returns. This study is carried out on companies that undertake stock split on Indonesia Stock Exchange (IDX). The sampling technique used is purposive sampling. The study involves 41 companies that conduct a stock split on the Indonesia Stock Exchange. Data analysis techniques used in this research is linear regression. The result of this study shows that the profitability proxied using the earning per share indicator and return on investment has a significant effect on stock returns. Meanwhile, the stock split is also found has a significant effect on stock return. The result of this study indicates that companies that have higher profitability will provide high stock returns to shareholders. Besides, companies that conduct stock splits receive higher stock returns than companies that are not.